(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Field experiments were carried out at Hudeiba ResearchStation Farm during 2004/ 05 and 2005/06 seasons to evaluate the effectof the location of infection source on the spread of onion yellow dwarfvirus (OYDV) and to screen 18 onion genotypes for resistance to thevirus. Disease incidence was assessed in blocks of 60 x 6 m planted withdisease-free onion seedlings and located upwind and downwind of thedisease source at distances of 0, 6, 12, 18, 24 and 30 m. Averageincidence of 33.7% and 57.8% was recorded in downwind blockscompared to 8.0% and 9.9% in upwind blocks, irrespective of the distancefrom the disease source, in 2004/05 and 2005/06, respectively. The blockslocated downwind and adjacent to the disease source had the highestdisease incidence of 93.4% and 95.5% compared with 7.8% and 18.9% inblocks located at a distance of 30 m away from the source during the twoseasons, respectively. In upwind blocks, disease incidence of 15.4% and20.2% was recorded in blocks adjoining the disease source, whileincidence of 3.7% and 4.85% was recorded in blocks located at a distanceof 30 m in the two seasons, respectively. None of the genotypes testedwas resistant to the OYDV infection; however, Baftaim Red genotypeproved to be tolerant to the virus.